TRENDS IN BREAST CANCER SURGERY IN PRIVATE PATIENTS UNDER OPPORTUNISTIC SCREENING - Oenning, Tatiane Aparecida; Correa, Juliana Lopes; Martins, Júlia Helena Alves Fortes; Souza, Michelli Esteves de; Barbosa, João Pedro Penteado; Dória, Maíra Teixeira; Furlan, Luiz Henrique; Sobreiro, Bernardo; Úrban, Cícero; Rabinovich, Iris; Furlan, Karina; Spautz, Cleverton; et al. (Mastology, 2019)
Objective: This study aims to determine the evolution of staging and surgical treatment in patients with breast cancer in a private clinic over the last 40 years. Methods: Retrospective descriptive observational study, through statistical analysis of the medical records of 2105 patients treated at a private clinic in Curitiba, Paraná, between 1977 and 2017. Results: Data analyzed from 2,105 patients diagnosed with breast cancer revealed that, over time, radical surgeries predominated when compared to conservative ones. However, when analyzed proportionally over the years, it is possible to observe an inversion of the surgical modalities. It was demonstrated that from 1977 to 2017, there was a 273% increase in the number of conservative surgeries and a 45.5% decrease in mastectomies. In addition to this data, there was a decrease in the number of axillary emptying and, consequently, of positive sentinel lymph nodes. In addition, tumors diagnosed early (T1) have increased over the years. Conclusion: Patients had an early diagnosis of the disease, resulting in less invasive surgical treatments and, consequently, lower morbidity and mortality.